2021
DOI: 10.21203/rs.3.rs-666723/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cytokine Profiles in the Detection of Severe Lung Involvement in Hospitalized Patients With COVID-19: the IL-8 – IL-32 axis

Abstract: Coronavirus disease 2019 (COVID-19) is an infectious respiratory disorder caused by a new coronavirus called SARS-CoV-2. The pathophysiology of severe COVID-19 is associated with a “cytokine storm”, characterized by anomalous release of various pro-inflammatory cytokines which contribute to alveolar exudation and lung damage. Overproduction of the proinflammatory cytokines IL-1, IL-6, IL-8 and TNF-α and low of expression IFN-γ have been found in severe COVID-19 patients. The mechanism by which IL-32 exerts its… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 17 publications
3
4
0
1
Order By: Relevance
“…These findings were in contrast with a study showing IL-32 concentration was significantly higher in healthy subjects than COVID-19 patients. 8 However, our data were consistent with reports revealing IL-32 level had an increase in patients with non-severe COVID-19 compared with those suffering from severe disease. 8 Furthermore, it is speculated that IL-32 along with other cytokines may contribute to the increased occurrence of atherosclerosis observed in COVID-19 patients.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These findings were in contrast with a study showing IL-32 concentration was significantly higher in healthy subjects than COVID-19 patients. 8 However, our data were consistent with reports revealing IL-32 level had an increase in patients with non-severe COVID-19 compared with those suffering from severe disease. 8 Furthermore, it is speculated that IL-32 along with other cytokines may contribute to the increased occurrence of atherosclerosis observed in COVID-19 patients.…”
Section: Discussionsupporting
confidence: 92%
“…8 However, our data were consistent with reports revealing IL-32 level had an increase in patients with non-severe COVID-19 compared with those suffering from severe disease. 8 Furthermore, it is speculated that IL-32 along with other cytokines may contribute to the increased occurrence of atherosclerosis observed in COVID-19 patients. 17 Other studies on influenza A virus infection, a disease with similar pathogenesis to COVID-19, have revealed that IL-32 production was triggered by influenza A virus in human peripheral blood mononuclear cells (PBMCs) from healthy volunteers and, in turn, reduced viral replication.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations